MODIFIED SRIMPI WEDDING PERFORMANCES in PEKALONGAN, CENTRAL JAVA - , VEBRIAN PUJI A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper aims to analyze wedding Pekalongan style, where there are various elements of wedding ritualsuntilpekalongan bridal makeup. In essence, this paper will focus on the elements contained in Pekalongan style wedding. These elements include the history, implementation procedures and steps, bridal makeup and bridal costumes. The collection of data and information on the topics covered, the authors conducted several methods including the review of relevant literature to the informant interviews, and Internet media. Improved overview of the literature that the author uses several books as a theoretical basis. Interviews conducted directly to the bridal beauticians to obtain real data. Search resources over the internet done to get the articles related to the topic discussed Based on direct observation, interviews and case studies, Srimpi wedding has elements covering :ngetuklawang, ngentenijawaban, sang-sangan, ngirimpliwat, ijabqobul, and resepsi. Meanwhile Srimpi weddingpekalongan style characterized by capiturang on the bride's makeup.